In Search of Mobile Applications for Urogynecology Providers. Issue 6 (November 2019) - Wallace, Shannon L.; Mehta, Shailja; Farag, Sara; Kelley, Robert S.; Chen, Katherine T.
Abstract : Introduction: Thousands of medical applications (apps) are available for mobile devices. Finding accurate, health care provider–centered apps may be time consuming and frustrating for urogynecologists. The objective of this study was to identify and evaluate urogynecology (urogyn) apps using a modified APPLICATIONS scoring system. Materials and Methods: Urogyn apps were identified from the Apple iTunes and Google Play Stores using the following 10 MeSH terms: urogynecology, incontinence, prolapse, urinary tract infection, pelvic surgery, fecal incontinence, defecation disorder, voiding disorder, urethral diverticulum, and fistula . Patient-centered and inaccurate apps were excluded. The remaining apps were evaluated with a modified APPLICATIONS scoring system, which included both objective and subjective criteria to determine each app's ability to aid in clinical decision making and to provide informational data. Objective rating components were price, paid subscription, literature referenced, in-app purchases, Internet connectivity, advertisements, text search field, interplatform compatibility and incorporated images, figures, videos, and special features. Subjective rating components were ease of navigation and presentation. Results: Our search yielded 133 and 235 apps in the Apple iTunes and Google Play Stores, respectively. Only 8 apps (4 of which were in both stores) were determined to be accurate and useful; these were evaluated using the modified APPLICATIONS scoring system. The top-rated app was Practical Urology. Conclusion: Few accurate clinical decision-making and informational apps exist for urogynecologists. Apps varied by comprehensiveness and quality. This study highlights the importance of systematically reviewing and rating medical apps. It also emphasizes the need for developing accurate apps for urogynecologists that improve health care provider performance and patient outcomes. Abstract : This study identified and evaluated apps for urogynecologists using a modified APPLICATIONS scoring system.